Integrated agroecological rice fish farming in Andhra Pradesh, India: A case study - Samaddar, Ayan; Panemangalore, Arun Padiyar; Maliappan, Sudharsan; Borah, Gulshan; Sikka, Alok; Kumar, Gopal (2024)
Andhra Pradesh is known as the "Rice Bowl of India" since its primary crop for commerce is rice. On the other hand, there is a current demand for alternative non-chemically dependent technology to ensure sustainability in both the economy and the environment. In order to alter the rice production system in alignment with fish and horticultural crops under an Integrated Farming System (IFS), Rythu Sadhikara Samstha (RySS) adopted the integrated rice-fish culture system as part of the Andhra Pradesh Community Managed Natural Farming (APCNF) initiative. In such a system, aquaculture is currently receiving greater attention due to its growing demand and favourable production economics requiring less effort. An initial evaluation was carried out by analyzing the physico-chemical characteristics of the water, the planktonic assemblages in water, types of inputs used, costs, results, and the pertinent farmer reactions on eight randomly selected IFS-based aquaculture system. This study demonstrated that integrating fish production in rice fields is a viable, low-risk, and ecologically friendly supplementary economic activity, offering numerous advantageous, including enhanced incomes and a better supply of fish for rural agricultural communities. However, for development and extension agencies to facilitate the adoption and benefits of this model among small and marginal farmers, careful consideration of this system is imperative. It would be interesting and crucial for future research to determine the optimal fish stocking density and input distribution in terms of productivity, survival rate, and biodiversity. Ultimately, investigating how rice-fish coculture methods contribute to the aquatic environment and biodiversity may reveal new pathways to promote the agroecological transition of the system.